ChemInform Abstract: Synthesis and Optical Properties of Dithienostiboles. Issue 7 (22nd February 2013) - Ohshita, Joji; Fujita, Risa; Tanaka, Daiki; Ooyama, Yousuke; Kobayashi, Norifumi; Higashimura, Hideyuki; Yamamoto, Yohsuke
Abstract Dithienostiboles having a stibole ring fused with a bithiophene system are prepared for the first time.